[PP.16.10] WHICH MEASUREMENT OF BLOOD PRESSURE IS MORE ASSOCIATED WITH ATHEROSCLEROTIC CARDIOVASCULAR DISEASE WITHOUT HYPERTENSION: CENTRAL BLOOD PRESSURE OR PERIPHERAL BLOOD PRESSURE?. (September 2016) - Kim, G.; Moon, D.; Lee, S.N.; Kim, J.H.; Moon, K.W.; Yoo, K.D.; Kim, C.M.
Abstract : Objective: Peripheral systolic blood pressure (pSBP) has been used to predict atherosclerotic cardiovascular disease (ASCVD). However, the assessment of superiority between pSBP and central SBP (SBP2) to predict ASCVD in patients without hypertension (HTN) has not been fully established. Design and method: Nine hundred and eighteen patients (male:female ratio 700:218, mean age 54.7 ± 13.7 years) without HTN were enrolled from subjects who received non-invasively semiautomated radial artery applanation tonometry (using an Omron HEM-9000AI) in the Department of Internal Medicine, St. Vincent's Hospital, from July 2011 to May 2015. Moreover, the area under the receiver operating characteristic curve (AUC) of SBP2 was compared with that of SBP to identify ASCVD. Results: Two hundred and eighteen subjects (male:female ratio 131:82, mean age 61.7 ± 11.1 years) were diagnosed as ASCVD according to coronary angiography or coronary CT scan. Interestingly, ASCVD patients had significantly lower pSBP (124 ± 18 mmHg vs 128 ± 17 mmHg) and SBP2 (114 ± 18 mmHg vs 118 ± 18 mmHg) than the patients without ASCVD. However, ASCVD patients had significantly higher pulse pressure (52 ± 13 mmHg vs 50 ± 12 mmHg) than the patients without ASCVD. After multivariate analysis after adjusted for age, gender, body mass index, fasting plasma glucose, diabetes, lipid profiles, antihypertensive medication and lipid-lowering medication, SBP2 (β = 0.231, 95% CI 1.036 to 1.289, p = 0.010) or pSBP (β = 0.887, 95% CI 0.800 to 0.982, p = 0.021) were associated with ASCVD. In addition, AUC of pSBP was significantly greater than that of SBP2 to identify ASCVD (P = 0.035). Conclusions: Central blood pressure is superior to pSBP in identifying ASCVD, although both peripheral and central SBP are associated with ASCVD in patients without hypertension.